Efficient frequency regulation in highly penetrated power systems by renewable energy sources using stochastic fractal optimiser - El-Hameed, Mohamed A; Elkholy, Mahmoud M; El-Fergany, Attia A (IET renewable power generation, 2019)
The study proposes efficient controllers to regulate frequency in highly penetrated power systems by renewable energy sources. Frequency controllers for variable speed wind turbines are designed to extract the stored energy in rotating masses, and efficiently regulate the pitch angle for frequency support. A temporary fast participation of storage battery incorporated with photovoltaic sources is provided via auxiliary controller. Controllers' fine tuning is realised by using stochastic fractal optimiser (SFO). The integral time absolute error in area frequency and tie line power represents the adapted objective function subjects to set of constraints. The performance assessments are carried out in three phases: (i) at initial stage, the secondary control is disabled and impact of wind penetration level on frequency nadir and frequency deviations are investigated, (ii) coordinated inertia/energy storage control is demonstrated, and (iii) finally, robustness analysis is made considering system parametric variations and real weather data. The proposed control strategy is verified by simulation in MATLAB/SIMULINK environment. The drawn numerical results by the SFO are compared with those achieved by genetic algorithm and the built-in controller tuner in SIMULINK. Performance assessments, comparative study along with robustness analysis of the SFO results confirm its viability and effectiveness.